Tahar L’étudiant . Tahar the Student - Mennegun, Cyril (Zadig productions, 2005)
Verzio FF submission Tahar is one of the sixty thousand students of Montpellier. Far from clichés, Tahar gives us to see the precariousness of a scholarship holder and the solitude reigning on university campuses. He shows us how difficult it is to find a job and the necessity to beg some food to overwhelmed associations. The film is indeed about it, about a young French today, stemming from the immigration, as usually said. About a student in search of a "tomorrow, which belongs only to him".